Menumbuhkan Motivasi Berprestasi pada Siswa Kelas X di SMKS Reformasi : Sebuah Studi Kasus - Parmianti Parmianti (Universitas Palan, 2025)
This study aims to identify the factors influencing the low achievement motivation of Grade X students at SMKS Reformasi. Using a qualitative approach with a case study method, data were collected through interviews, observations, and questionnaires. The findings reveal that social support from teachers and parents significantly impacts students' motivation. However, a lack of recognition for achievements, insufficient learning challenges, and the relevance of learning to career goals pose major barriers to improving student motivation. This study provides recommendations for strategies to create a more conducive learning climate, structured rewards, and learning aligned with students' needs.